Melacak Jejak Islamisasi Pangeran Dipanegara di Kecamatan Pajangan Kabupaten Bantul Daerah Istimewa Yogyakarta - Mundzirin Yusuf (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2016)
Prince Dipanegara when he was child called as Bendoro Raden Mas Ontowiryo, born in Yogyakarta, 11 November 1785 and died in Makasar South Sulawesi, 8 January 1855. He was as the first son of Hamengku Buwono III, and his mother’s name  Raden Ajeng Mangkarawati. Because of her kindness in Java war, she received designation as the national hero. The heritage trail of Islam which was done by Dipanegara was still available and could be found to the present, even though in the form of pieces. In example, stone relief for pedestals of mosque. Now, the relief stones are used for pedestals and put in front of the male cave. It is used for sitting place for the visitors.            This research uses history method in which located around of  Pajangan District. The theory used here is change and response from Arnold J. Toynbee. Then the researcher uses behavioral approach.  This method is not only related to one event but also address to the historical actor and real situation. During the Islamic process, Dipanegara got support from his loyal followers and also supported by people around this place.